ADMINISTRATION OF BEE POLLEN INCREASED OF PRIMARY SPERMATOCYTE COUNT AND IMPROVE THE QUALITY SEMINIFEROUS TUBULE IN MALE WHITE RATS WHICH EXPOSED TO CIGARETTE SMOKE - Hermawan, Febe Adonia Renandra; Laksmi, Desak Nyoman Dewi Indira; Bebas, Wayan (Buletin Veteriner Udayana, 2022)
This study aims to determine the effect of bee pollen on increasing the number of primary spermatocytes and the quality of seminiferous tubules in white rats exposed to cigarette smoke. This research is a study that uses a RAL research design (Completely Randomized Design). The samples in this study were male white rats aged 3-4 months with a body weight range of 200 grams, as many as 18 rats were divided into three groups, namely 6 rats in the control group, 6 rats in the P1 group, and 6 rats in the P2 group. P0 = the group without bee pollen was exposed to cigarette smoke, P1 = the group given one dose of bee pollen was exposed to cigarette smoke, and P2 = the group with two doses of bee pollen was exposed to cigarette smoke. All rats were given an adaptation period of one week, then treated for 42 days. On day 43, the rats will be necropsied and the histology of the seminiferous tubules will be seen. The results showed that there was a significant increase in the number of primary spermatocytes and the quality of the seminiferous tubules on bee pollen administration. From the results of this study, it can be concluded that the administration of bee pollen can increase the number of primary spermatocytes and improve the quality of the seminiferous tubules in rats exposed to cigarette smoke. From the results of this study, it is necessary to conduct further research to measure the levels of free radicals in the testicular tissue of white rats exposed to cigarette smoke in their reproductive system.